Effect of filler wire strength on high strength low alloy steels. (2022) - John, Merbin; Kumar, P. Ashok; Bhat, K. Udaya
Abstract: Fusion welding of Ti-Nb microalloyed steels often leads to softening in the heat affected zone (HAZ) due to weld thermal cycles. Apart from heat input and width of HAZ, selection of filler wire also plays an important role, to achieve the minimum strength requirement of the parent material. Steel plates with 800 MPa ultimate tensile strength were butt welded using pulsed gas metal arc welding (P-GMAW) process, with undermatching, matching and overmatching strength filler wires. Welding parameters were selected in such a way that the heat input per unit weld length is almost constant. In all the samples, microstructural features were similar in the HAZ region. Static tensile tests indicated that failure in the samples welded using undermatching filler occurred at welded region, whereas the samples welded with matching and overmatching fillers failed at HAZ region. Further fracture studies indicated that, in case of under matching filler wire samples, crack propagates along the Widmanstatten ferrite present in the weld zone, whereas in other two samples, crack initiated at coarse TiN – matrix interface in the HAZ region. This study shows that overmatching fillers are recommended to overcome strength loss due to HAZ softening.